Liquidity Management on The Performance of Listed Insurance Companies in Nigeria - Oluwatobi Fasheyitan David; Ikpefan Ochei Ailemen; Alex Adegboye (Communications of International Proceedings, 2022)
A business's viability and success is largely influenced by its liquidity management style and control. This is because either inadequate or excess liquidity may impair the smooth operation of the business. This apparent problem has sparked considerable interest in issues of the management of liquidity in the context of significant financial outlays. However, diagnosis has been scarce in the insurance industry. Thus, the article's objective is to investigate how liquidity impacts the entire performance that results in financial efficiency. The research is based on a sample of ten insurance companies that were publicly traded on the Nigerian Stock Exchange from 2013 to 2019. Using a random effect panel regression model, this research discovered that liquidity management had a strong negative correlation with financial performance metrics in Nigeria's insurance industry. However, just a single positive coefficient was observed with current ratio affects performance in relation to ROA, while ROE was automatically insignificant when the same variables were used. Additionally, what set this investigation apart was the inclusion of economic factors that had no impact on the research. The study concludes, among other things, that given the volatility or risk level connected with insurance companies' services, it is critical for them to constantly invest in accessible assets regardless of the associated cost of payment or in meeting their commitments.
Keywords: Liquidity; Financial performance; Management; Insurance Company.